Collective action and property rights for poverty reduction: A synthesis - Mwangi, Esther; Markelova, Helen; Meinzen-Dick, Ruth S. (University of Pennsylvania Press, 2011)
The major theoretical enterprise of this book is to understand how the institutions of collective action and property rights influence rural poverty and livelihoods. Their links to sustainable natural resource management (NRM) are relatively well established, but this does not necessarily translate into poverty reduction. To address this question, we also need to look at the inclusiveness of these institutions; how they are influenced by (lack of) assets, risks, and governance structures that favor or disfavor poor people; and how these institutions shape the resources and strategies that poor and nonpoor actors use to further objectives of meeting basic needs and increasing income, security, social and political inclusion, or sustainability. We do this through a series of case studies that applies an extended version of the Institutional Analysis and Development (IAD) framework; the IAD framework was originally developed to isolate and understand the function of institutions in NRM. In this chapter we reflect on the findings from the nine case studies presented in this volume.